What is -3 times x squared?-9x
C
If you plug in the values in that equation, it works.
Answer:
y = 4x - 12
Step-by-step explanation:
Please let me know if you want me to add an explanation as to why this is the answer/how I got this answer. I can definitely do that, I just wouldn’t want to write it if you don’t want me to :)
Answer:
-49
Step-by-step explanation:
In order to fill in the given expression, we need to know ...
- f(-2) = -4
- f(-3) = 5
- f(-4) = 7
- g(0) = -7
- g(-3) = 3
Then the expression is ...
√(5 -(-4)) -(-7)² +7÷(-7)·(3) = √9 -49 +7/(-7)(3)
= 3 -49 +(-1)(3) = 3 -49 -3
= -46 -3 = -49